Structures under Shock and Impact XVI - Syngellakis, S.; Schleyer, G. (WIT transactions on the built environment, 2020)
The included papers, presented at the 16th International Conference on Structures under Shock and Impact, highlight new research ideas and results to promote a better understanding of the critical issues relating to the testing behaviour, modelling and analyses of protective structures against blast and impact loading.